2012
DOI: 10.4236/ajps.2012.31011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Leaf Morphology in <i>Aster hispidus</i> Thunb. var. <i>leptocladus</i> (Makino) Okuyama (Asteraceae)

Abstract: The comparative morphology and anatomy of leaves in the serpentine endemic <i>Aster hispidus</i> Thunb. var. <i>leptocladus</i> (Makino) Okuyama and its close relative <i>A. hispidus</i> var. <i>hispidus</i> were examined. Our morphological analysis revealed that the leaves of <i>A. hispidus</i> var. <i>leptocladus</i> were significantly smaller and narrower than those of <i>A. hispidus</i> var. <i>hispidus</i>. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…The characteristic vegetation in serpentine outcrops is associated with the presence of edaphic endemic species, and the morphological characteristics may differ from those of ancestral species in non-serpentine areas (Kruckeberg, 1954). In fact, previous studies have indicated that serpentine-adapted plants have narrow leaves (Hayakawa et al, 2012;Ohga et al, 2012;Kumekawa et al, 2013Kumekawa et al, , 2016, indicating that these reductions could be a response to an edaphic environment that exhibits nutrient deficiencies in serpentine soils (Kruckeberg, 1954). Our results indicated that E. japonica in the serpentine populations had thicker leaves and smaller stomata than those of the inland populations (Table 2), suggesting that E. japonica had been morphologically and anatomically modified to adapt to serpentine soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic vegetation in serpentine outcrops is associated with the presence of edaphic endemic species, and the morphological characteristics may differ from those of ancestral species in non-serpentine areas (Kruckeberg, 1954). In fact, previous studies have indicated that serpentine-adapted plants have narrow leaves (Hayakawa et al, 2012;Ohga et al, 2012;Kumekawa et al, 2013Kumekawa et al, , 2016, indicating that these reductions could be a response to an edaphic environment that exhibits nutrient deficiencies in serpentine soils (Kruckeberg, 1954). Our results indicated that E. japonica in the serpentine populations had thicker leaves and smaller stomata than those of the inland populations (Table 2), suggesting that E. japonica had been morphologically and anatomically modified to adapt to serpentine soils.…”
Section: Discussionmentioning
confidence: 99%
“…var. leptocladus (Makino) Okuyama (Asteraceae) (Hayakawa et al, 2012;Kumekawa et al, 2013) and have been considered a plant adaptive mode in serpentine areas. Moreover, the fact that the reduced stomatal density was also found among different lineages suggested that this modification was likely an adaptation to serpentine areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, the leaf index differed significantly between the two investigated serpentine areas. Hayakawa et al (2012) observed that the leaf index of the serpentine species, Aster hispidus var. leptocladus, differed according to serpentine areas, and proposed that leaf morphology was involved not only in stenophyllization, but also in minitualization.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these species have morphological characteristics such as narrower leaves and thinner stems. For example, Hayakawa et al (2012) demonstrated that the narrow leaf of the serpentine endemic Aster hispidus Thunb. var.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, these varieties could be result of ecotypic differentiation in A. hispidus in Japan driven by different ecological factors prevailing in the habitats it occupied. To substantiate the premise, the study by Hayakawa et al (2012) involving A. hispidus and of the stenophyllous A. hispidus var. leptocladus showed decreased cell number of the horizontal axis of a leaf based as an adaptation.…”
Section: Introductionmentioning
confidence: 99%